Ontology for New Media Hybridity - Fábio Waki (MatLit, 2017)
Review of Jihoon Kim, Between Film, Video, and the Digital: Hybrid Moving Images in the Post-media Age, New York: Bloomsbury, 2016, 404 pp., ISBN 978-1-6289-2293-6.